Science Teachers’ Readiness in Professional Training Programs for Sustainability-Oriented STEM Education (Journal of Science Learning, 2026)
Integrating Science, Technology, Engineering, and Mathematics (STEM) with sustainability-oriented education is essential to preparing students to address global environmental and social challenges. Teacher readiness is a key factor in successful implementation, yet there is limited evidence about its current state in Indonesia. This study examined science teachers' readiness to implement sustainability-oriented STEM education, explored the influence of professional development experiences, and identified challenges and opportunities in classroom practice. The study used quantitative and qualitative data from 112 science teachers who completed a structured questionnaire with closed- and open-ended questions. Quantitative analysis included descriptive statistics, correlation analysis, radar plot visualization, and independent sample t-tests, while qualitative data were analyzed thematically. Findings showed that teachers demonstrated a moderate level of readiness, with high internal consistency across constructs. Correlation analysis revealed significant relationships among readiness dimensions, and the radar plot indicated stronger profiles in knowledge and skills but weaker outcomes in professionalism and collaboration. The inferential results highlighted that participation in ESD training significantly enhanced readiness with a moderate-to-large effect size, whereas STEM training alone did not. Thematic analysis generated seven themes: professional development, resources, curriculum, collaboration, knowledge, attitudes, and barriers. Teachers expressed enthusiasm for implementing sustainability-oriented STEM education but noted systemic constraints, including limited training, inadequate resources, heavy workloads, and insufficient institutional support. The study concludes that strengthening professional development programs focused on sustainability, improving facilities, aligning curricula, and fostering collaboration are critical to advancing teachers' readiness to integrate sustainability principles into STEM education meaningfully.